Pengklonan dan pencirian klon cukmcsKMCS yang mengekodkan kapsaisin sintase (Cs) - Nurul Hikma Md Isa,; Ismanizan Ismail,; Zamri Zainal, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Capsaicinoid, the main alkaloid compound that gives pungent taste to peppers is restricted to the genus of Capsicum. It consists of two major components which are capsaicin and dihydrocapsaicin. Here we reported the isolation of capsaicin synthase (Cs) cDNA via RT-PCR method and the resulting cloned was named as CUKMCS with the expected size of 981 bp. Homology search via the blastx and blastp program from the NCBI database showed that CUKMCS has a high homology to the Cs in Capsicum frutescens, Capsicum annuum and Capsicum chacoense. The predicted size of CUKMCS protein is around 36 kDa. Transcripts expression in 5 different tissues revealed that Cs transcripts were detected in the placental tissue, mesocarp and seed while no corresponding expression was detected in the leaf and root.